The Composition of Complexes between Plasminogen Activator Inhibitor 1, Vitronectin and either Thrombin or Tissue-type Plasminogen Activator - van Meijer, Marja; Stoop, Allart; Smilde, Annelies; Preissner, Klaus T; van Zonneveld, Anton-Jan; Pannekoek, Hans (Thrombosis and Haemostasis, 1997)
Vitronectin (VN) is an obligatory cofactor for the inhibition of thrombin by plasminogen activator inhibitor 1 (PAI-1). It accelerates the rate of association between thrombin and PAI-1 more than two orders of magnitude. In contrast, VN does not accelerate the association between tissue-type plasminogen activator (t-PA) and PAI-1. Previously, we reported that the anti-PAI-1 monoclonal antibody (MoAb) CLB-2C8 binds to a short stretch of amino acids of PAI-1, located between residues 128 and 145, and prevents PAI-1 binding to VN. Furthermore, MoAb CLB-2C8 fully blocks the inhibitory activity of PAI-1 towards t-PA, emphasizing the importance of this area for the interaction with t-PA. Here, we show that this area is also required for the interaction between thrombin and PAI-1, since MoAb CLB-2C8 fully prevents inhibition of thrombin by PAI-1. In spite of similar structural requirements for the interaction between t-PA, PAI-1 and VN and between thrombin, PAI-1 and VN, the intermediate reaction products are clearly distinct. By employing surface plasmon resonance (SPR), using the BIAcore equipment, and by immunoprecipitation we demonstrate that, in the presence of VN, t-PA and PAI-1 form exclusively equimolar binary t-PA/PAI-1 complexes. Thrombin, PAI-1 and VN generate equimolar, binary thrombin/PAI-1 complexes and in addition equimolar, ternary complexes and multimers.